Intelligent DevOps : Leveraging AI to Revolutionize Software Delivery - Apurva Reddy Kistampally (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the transformative impact of artificial intelligence on DevOps practices and software delivery methodologies, presenting a comprehensive analysis of current implementations, challenges, and future directions. The article explores how AI-driven solutions are revolutionizing traditional DevOps workflows through advanced automation, predictive analytics, and intelligent decision-making systems. Key focus areas include the optimization of CI/CD pipelines through pattern recognition and machine learning algorithms, the enhancement of code quality through automated review systems, and the implementation of predictive analytics for proactive risk management in release cycles. The article delves into practical applications of AI in testing automation, user behavior simulation, and anomaly detection while addressing critical considerations such as model drift management and integration complexities. Through article analysis of industry implementations and emerging trends, this article demonstrates how organizations can achieve significant improvements in deployment efficiency, code quality, and operational reliability through AI-DevOps integration. The article indicates that organizations implementing AI-driven DevOps practices have experienced substantial reductions in deployment failures, accelerated release cycles, and enhanced software quality metrics. This article provides valuable insights for practitioners and researchers seeking to understand and implement AI-powered DevOps solutions while navigating the associated technical and organizational challenges.